2016
DOI: 10.1007/s10995-016-2033-x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Infant Feeding Practices on Infant Mortality in Southern Africa

Abstract: Objective To examine the adjusted and unadjusted effects of infant feeding practices on infant mortality in Southern Africa. Methods A merged dataset from the most recent Demographic and Health Surveys for Lesotho, Swaziland, Zambia and Zimbabwe was analysed using the Cox Proportional Hazard Model. A total number of 13,218 infants born in 5 years preceding all the surveys with information on infant feeding practices constituted the study population. Infant mortality was the outcome variable and infant feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
3
0
2
Order By: Relevance
“…Mothers who have male babies are more likely to have a higher risk of infant mortality than female babies. It is in line with research in South Africa that revealed that female infants tend to have a lower risk of infant mortality than male babies (Motsa et al, 2016). Previous research has shown a higher relationship between infant mortality in males than in females (Sovio et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Mothers who have male babies are more likely to have a higher risk of infant mortality than female babies. It is in line with research in South Africa that revealed that female infants tend to have a lower risk of infant mortality than male babies (Motsa et al, 2016). Previous research has shown a higher relationship between infant mortality in males than in females (Sovio et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…The duration of breastfeeding in the first six months is one of the predictors of a significant reduction in infant mortality (Oktaria et al, 2017;Sankar et al, 2015). A study in South Africa showed that exclusive or partial breastfeeding reduces the risk of infant mortality (Motsa et al, 2016) This study found that maternal education has a significant effect on infant mortality in rural Indonesia. Mothers with higher secondary education are more likely to experience infant survival than mothers with primary or uneducated education in rural Bangladesh (Akter et al, 2015).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Beberapa penelitian menyebutkan bahwa masalah gizi pada bayi dan anak disebabkan kebiasaan ASI dan MP-ASI yang tidak tepat (kuantitas dan kualitas). Selain itu, adanya kebiasaan pemberian makanan bayi yang tidak tepat seperti: pemberian makanan yang terlalu awal atau terlambat, makanan yang diberikan tidak sesuai porsi dan frekuensi yang kurang (Motsa, Ibisomi, & Odimegwu, 2016). Pemberian makanan yang terlalu lambat akan menyebabkan bayi mengalami kesulitan mengunyah, tidak menyukai makanan padat dan kekurangan gizi.…”
Section: Pendahuluanunclassified
“…Breastfeeding (BF) is "natural" and "best feed" for infants since evaluation of mankind. Exclusive BF not only helps in bringing down the mortality and morbidity during infancy but is also helpful to mothers in many ways [1,2]. BF is evidence based intervention that has been found to be significantly reduced the neonatal as well as child mortality by 13% [3].…”
Section: Introductionmentioning
confidence: 99%